Pengaruh Literasi Ekonomi terhadap Minat Berwirausaha Peserta Didik Kelas XI IPS SMA Negeri 38 Jakarta - Silviana Silviana; Windi Megayanti (Neolectura, 2022)
Economy is a factor that plays an important role in human life. As a result of the emergence of Covid-19 has an impact on all aspects of life, one of which is in the economic field. Problems that arise include the disruption in labor conditions, namely the increasing number of unemployment. Entrepreneurship can help reduce unemployment. To start entrepreneurship can not be instant but targeted by the existence of interest. The number of entrepreneurship ratios in Indonesia itself is still quite low compared to other ASEAN countries. In addition, economic activity refers to the extent to which economic actors have and understand knowledge about the economy. The level of understanding of economic literacy in each community is different. In fact, the level of financial literacy which is part of the national economic literacy is still relatively low. This study aims to determine the effect of economic literacy on interest in entrepreneurship. This study uses descriptive research with a quantitative approach. This research was conducted at SMA Negeri 38 Jakarta in February - June 2022. The population in this study were students of class XI IPS SMA Negeri 38 Jakarta, totaling 120 students. The number of samples as many as 92 students were taken using simple random sampling technique. Methods of data collection using observation, tests, questionnaires, and documentation. The data analysis technique used is simple linear regression and hypothesis testing. The linear regression value for this study is Y = 62.46 + 0.212X. Based on the results of statistical calculations, it is known that there is an influence between economic literacy on students' entrepreneurial interests.